Penerapan Enterprise Risk Management (ERM) Berdasarkan COSO-Framework Pada Perusahaan Manufaktur di Indonesia - Hidayah, Nur Sabrina; Pradesa, Hafid Aditya; Taufik, Nur Imam; Purba, Caesar Octoviandy; Agustina, Iin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Enterprise risk management (ERM) is essential for companies to mitigate uncertainties in today's business environment, enabling them to focus on achieving strategic goals and objectives. This study aims to analyze the disclosure level of ERM and the influence of company size and industry sector on manufacturing companies listed on the Indonesia Stock Exchange (IDX). Employing a purposive sampling method, 29 manufacturing companies listed on the IDX were selected as the analysis units for this research. Utilizing secondary data collected from annual reports over a three-year period (2019–2021), ERM index assessments were conducted based on the COSO framework content. The research findings generally indicate significant variations in ERM disclosure, with larger companies demonstrating higher levels, while the industry sector showed no significant influence. ERM implementation revealed an increasing trend, particularly in risk identification and response, although stagnation was observed in other components. Most companies met the minimum disclosure requirements, but transparency regarding financial risks and audit budgets was lacking. The level of ERM implementation varied, influenced by company size, risk profile, and company status. This study emphasizes the importance of comprehensive ERM disclosure as a positive signal for investors and recommends enhancing overall ERM implementation along with more transparent disclosure of financial risks. Further research is suggested to explore additional factors and their impact on firm performance.